Comprehensive experimental study of NBνN barrier structures based on n-HgCdTe MBE for detection in MWIR and LWIR spectra - Voytsekhovskiy, Alexander V.; Dzyadukh, Stanislav M.; Gorn, Dmitriy Igorevich; Dvoretsky, Sergei A.; Mikhailov, Nikolay N.; Sidorov, Georgiy Yu; Yakushev, Maxim V. (Physica scripta)
This work is devoted to a comprehensive experimental study of the electrical and photoelectric characteristics of barrier photosensitive structures in the NBνN configuration based on n-HgCdTe (MCT). Seven different types of photosensitive structures for middle wavelength (MWIR) and long wavelength (LWIR)infrared (IR)radiation ranges grown by molecular beam epitaxy (MBE) have been studied by complex conductivity spectroscopy method. The current-voltage characteristics(CVC) were measured both in the dark and in the presence of llumination. Based on the measured dependences of the dark current density on temperature and the ratio of the perimeter to the area of the structure, the dominant contribution of the bulk current component compared to the surface component for the MWIR structure (x∼0.30)was established. This fact was confirmed by the value of the activation energy (from the Arrhenius plots) corresponding to the band gap. The results of frequency measurements of the differential conductivity of MIS structures based on NBνN also give a close activation energy, which corresponds to the diffusion limitation. LWIR structures(x∼0.20) are characterized by an increase in the contribution of the surface leakage current in the total dark current. In this case, the activation energy determined from MIS measurements exceeds the band gap of the νlayer, which is associated with the presence of an energy barrier for holes in the valence band. It is shown that if the problem of passivation of mesa structures is solved, it is possible to fabricate efficient MWIR and LWIR nBn, NBνN detectors based on MBE HgCdTe with high threshold parameters.